2021
DOI: 10.1063/5.0045203
|View full text |Cite
|
Sign up to set email alerts
|

First-principle study of the structures, growth pattern, and properties of (Pt3Cu)n, n = 1–9, clusters

Abstract: In this work, a first-principles systematic study of (Pt3Cu)n, n = 1–9, clusters was performed employing the linear combination of Gaussian-type orbital auxiliary density functional theory approach. The growth of the clusters has been achieved by increasing the previous cluster by one Pt3Cu unit at a time. To explore in detail the potential energy surface of these clusters, initial structures were obtained from Born–Oppenheimer molecular dynamics trajectories generated at different temperatures and spin multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…As already mentioned, in Figure 1 , the found lowest energy structures for the (Pt 3 Cu) n , n= 1–11 nanoclusters were presented. The structures used for this investigation were found performing a rigorous study based on molecular dynamics simulations in different electron spin multiplicities [ 20 , 21 ]. At the found optimized geometry the MEP CPs and bond paths were calculated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As already mentioned, in Figure 1 , the found lowest energy structures for the (Pt 3 Cu) n , n= 1–11 nanoclusters were presented. The structures used for this investigation were found performing a rigorous study based on molecular dynamics simulations in different electron spin multiplicities [ 20 , 21 ]. At the found optimized geometry the MEP CPs and bond paths were calculated.…”
Section: Resultsmentioning
confidence: 99%
“…These results and the employed methodology were published in Refs. [ 20 , 21 ]. These studies demonstrated that in the most stable (Pt 3 Cu) n , n = 5–6 cluster structures, the formation of structural single octahedra moieties was observed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decade, bimetallic clusters or nanoparticles have received increasing attention owing to their different physical and chemical properties compared with their pure counterparts [1][2][3][4][5][6][7][8][9][10]. Due to their unique properties, these clusters can be utilized for various technological applications in the fields of catalysis, electronics, and medicine, among others [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%